Estrategias creativas y metacognitivas en el aprendizaje musical. (2016)
This article explores the relationships between musical performance and metacognitive development of musical literacy students at the School of Arts and Music at Universidad Sergio Arboleda. The field of interest is centered on a pilot that includes creative procedures, processes of musical transcription, transfer to other curricular domains and use of emerging knowledge of the culture of the student as valuable components for contextualized learning. It is concluded that there is a close positive link between musical performance and metacognitive processes. A fact that benefits the qualifications of the teaching skills of teachers and student learning.